Dynamic control of NMDA receptor Ca 2+ permeability by endogenous and synthetic modulators - Mae G. Weaver; Gabriela K. Popescu (Proceedings of the National Academy of Sciences, 2025)
NMDA receptors are principal sources of postsynaptic Ca 2+ in central neurons. It is widely assumed that the content of Ca 2+ in the glutamate-elicited ionic flux is determined by the molecular composition of the NMDA receptors, whose expression varies developmentally and across brain regions and can change on a scale of minutes to hours. Here, we report that rather than being a fixed property of a given receptor assembly, the amount of Ca 2+ in the NMDA receptor current can fluctuate in real time over a wide dynamic range in response to endogenous and synthetic allosteric modulators. We identify the extracellular N-terminal domain of the receptor as a structural modulator of its Ca 2+ permeability and demonstrate that the mechanism involves changes in the receptor’s unitary Ca 2+ conductance. These results reveal an unsuspected lever controlling the NMDA receptor–mediated Ca 2+ transients and, implicitly, the many physiological and pathological processes influenced by these currents.